Bone marrow lympho-myeloid malfunction in obesity requires precursor cell-autonomous TLR4 - Liu, Ailing; Chen, Minhui; Kumar, Rashmi; Stefanovic-Racic, Maja; O’Doherty, Robert M.; Ding, Ying; Jahnen-Dechent, Willi; Borghesi, Lisa (Nature communications, 2018)
Obesity, a prevalent condition in adults and children, impairs bone marrow (BM) function. However, the underlying mechanisms are unclear. Here, we show that obese mice exhibit poor emergency immune responses in a toll-like receptor 4 (TLR4)-dependent manner. Canonical myeloid genes ( Csf1r , Spi1 , Runx1 ) are enhanced, and lymphoid genes ( Flt3 , Tcf3 , Ebf1 ) are reduced. Using adoptive transfer and mixed BM chimera approaches we demonstrate that myeloid>lymphoid bias arises after 6 weeks of high-fat diet and depends on precursor cell-autonomous TLR4. Further, lean mice exposed to the TLR4 ligand lipopolysaccharide (LPS) at doses similar to that detectable in obese serum recapitulates BM lympho-myeloid alterations. Together, these results establish a mechanistic contribution of BM cell-intrinsic TLR4 to obesity-driven BM malfunction and demonstrate the importance of LPS. Our findings raises important questions about the impact of maternal obesity and endotoxemia to fetal hematopoiesis, as fetal immune precursors are also sensitive to TLR4 signals. Obesity can affect bone marrow cell differentiation and the generation of myeloid and lymphoid cells. Here, the authors show that diet and obesity, as well as low-dose lipopolysaccharide, can alter Toll-like receptor 4 signaling bone marrow cells to skew the myeloid-lymphoid homeostasis in mice.